Inhibition of Metabotropic Glutamate Receptor Subtype 1 Alters the Excitability of the Commissural Pyramidal Neuron in the Rat Anterior Cingulate Cortex after Chronic Constriction Injury to the Sciatic Nerve. (September 2017) - Gao, Shi-Hao; Shen, Lin-Lin; Wen, Hui-Zhong; Zhao, Yan-Dong; Ruan, Huai-Zhen
Abstract : Background: Inhibition of the metabotropic glutamate receptor subtype 1 in the anterior cingulate cortex has an analgesic effect during sustained nociceptive hypersensitivity. However, the specific changes in different subtypes of anterior cingulate cortex layer 5 pyramidal neurons, as well as the distinct effect of metabotropic glutamate receptor subtype 1 inhibition on different neuronal subtypes, have not been well studied. Methods: Retrograde labeling combined with immunofluorescence, whole cell clamp recording, and behavioral tests combined with RNA interference were performed in a rat model of chronic constriction injury to the sciatic nerve. Results: Commissural layer 5 pyramidal neurons (projecting to the contralateral cortex) existed in the anterior cingulate cortex. The voltage-gated potassium channel subunit 2–mediated current in these neurons were substantially reduced after chronic constriction injury (current densities at +30 mV for the sham, and chronic constriction injury neurons were [mean ± SD] 10.22 ± 3.42 pA/pF vs. 5.58 ± 2.71 pA/pF, respectively; n = 11; P < 0.01), which increased the spike width and fast afterhyperpolarization potential, resulting in hyperexcitability. Inhibition of metabotropic glutamate receptor subtype 1 alleviated the down-regulation of voltage-gated potassium channel subunit 2 currents (current density increased by 8.11 ± 3.22 pA/pF; n = 7; P < 0.01). Furthermore, knockdown of voltage-gated potassium channel subunit 2 current in the commissural neurons attenuated the analgesic effect of metabotropic glutamate receptor subtype 1 inhibition (n = 6 rats; P < 0.05). Conclusions: The effect of metabotropic glutamate receptor subtype 1 inhibition on commissural anterior cingulate cortex layer 5 pyramidal neurons is likely different with the modification of previously studied hyperpolarization-activated/cyclic nucleotide-gated channel-dependent neurons but relies on the alteration of voltage-gated potassium channel subunit 2 currents. These results will contribute to a better understanding of the therapeutic role of metabotropic glutamate receptor subtype 1 in chronic pain. Abstract : In a rodent model of chronic constrictive injury, injury-induced hyperactivity of commissural fibers was associated with a reduction in voltage-gated potassium channel subunit 2–mediated current; metabotropic glutamate receptor inhibition produced an analgesic effect, restored voltage-gated potassium channel subunit 2 currents, and reduced hyperexcitability. The data support the notion that the analgesic efficacy of metabotropic glutamate receptor inhibition is in part mediated by reducing anterior cingulate cortex output to the contralateral cerebral cortex.